Cost-utility analysis: Current methodological issues and future perspectives - Mark J C Nuijten; Dominique J Dubois (Frontiers Media S.A., 2011)
The use of cost-effectiveness as final criterion in the reimbursement process for listing of new pharmaceuticals can be questioned from a scientific and policy point of view. There is a lack of consensus on main methodological issues and consequently we may question the appropriateness of the use of cost-effectiveness data in health care decision-making. Another concern is the appropriateness of the selection and use of an incremental cost-effectiveness threshold (Cost/QALY). In this review, we focus mainly on only some key methodological concerns relating to discounting, the utility concept, cost assessment and modelling methodologies. Finally we will consider the relevance of some other important decision criteria, like social values and equity.